”From score to sound” How to produce a sound using the techniques of audio engineering and reproducing composition without compromising the authentic content / Mohd Najib Abdul Shukor - Abdul Shukor, Mohd Najib (Faculty of Music, 2009)
Recording is a highly skilled craft combining art and science. It requires technical knowledge as well as musical understanding and critical listening ability. By learning these skills, you can capture a musical performance and reproduce it with quality sound for the enjoyment and inspiration of others. Your music and recordings will become carefully tailored creations of which you can be proud. They will be a legacy that can bring pleasure to many people for years to come.